Using Third Space and Literature Circles (TSLC) as transformative pedagogy for marginalized EFL learners - Awada, Ghada (2020)
We argue for a transformation in the current learning and literacy education of marginalized and nondominant groups of English- as- a Foreign Language (EFL) refugee learners in Lebanon. This paper describes the process of combining Third Space (TS) and Literature Circles (LC) to develop an instructional model of a transformative pedagogy for disadvantaged EFL learners in a transnational and challenging context. We report on how TSLC was used to address Human Rights Education (HRE) values, scaffold learners’ challenges, and develop their EFL proficiency. Feedback from teachers indicates that TSLC provides a learning zone for transforming learners’ negative experiences into stories of hope and envisioned better future. Likewise, teachers praised TSLC as an enjoyable and effective instructional strategy to engage and motivate learners as well as achieve curricular learning outcomes.